1982
DOI: 10.2136/sssaj1982.03615995004600030004x
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and Field Testing of a Two‐probe Gamma Gauge

Abstract: A series of laboratory and field calibration tests was carried out with a commercial double‐probe gamma gauge in an attempt to resolve difficulties encountered in routine field use of the equipment. The laboratory tests showed that transmitted count rate is affected by the extent of the medium surrounding the beam path, indicating that linearity between log of count rate and sample density is not sufficient proof of monochromatic radiation. The equipment was also found to be sufficiently sensitive to require t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Equation [3] in Rawitz et al (1982) was used to calculate bulk density using an unattenuated count rate (J 316000) and mass attenuation coefficients suggested by them for soil and water. Parallel Al access tubes 0.30 m apart were used to take measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Equation [3] in Rawitz et al (1982) was used to calculate bulk density using an unattenuated count rate (J 316000) and mass attenuation coefficients suggested by them for soil and water. Parallel Al access tubes 0.30 m apart were used to take measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Equation [3] presented by Rawitz et al (1982) was used to calculate bulk density using an unattenuated count rate (Jo = 316 000) and mass attenuation coefficients suggested by them for soil and water. Volumetric water content is part of the equation and was measured using a Troxler neutron probe.…”
Section: Plot Establishment and General Proceduresmentioning
confidence: 99%
“…By comparison, other studies have shown that bulk densities measured using a neutron-gamma surface gauge tended to be lower than the conventional ring method (e.g. Timm et al, 2005;Bertuzzi et al, 20 1987;Rawitz et al, 1982), although this difference was not statistically significant.…”
mentioning
confidence: 71%